Entrepreneurial innovation among international students in the UAE: Differential role of entrepreneurial education using SEM analysis - Shwedeh, Fanar; Adelaja, Ayotunde Adetola; Ogbolu, Gbemisola; Kitana, Abdelkarim; Taamneh, Abdallah; Aburayya, Ahmad; Salloum, Said A (International Journal of Innovative Research and Scientific Studies, 2023)
This paper explores the impact of entrepreneurial education among international students studying higher education in the UAE. The authors examine the role of entrepreneurial education as an independent variable and as a moderating variable in the relationship between external factors (measured by the economy, institutions and society) and internal factors (measured by entrepreneurial orientation, entrepreneurial capabilities and achievement) on entrepreneurial innovation. A survey approach was used in which predesigned questionnaires were distributed to the targeted respondents. We employed Structural Equation Modelling (SEM) analysis to analyze the collected data. The result reveals that exposing international students to entrepreneurial education is crucial to their entrepreneurial innovation. We also found the external and internal environments to be crucial factors that predict entrepreneurial innovation among the sample surveyed. Further findings revealed that entrepreneurial education significantly moderates the relationship between the external environment and entrepreneurial innovation whereas the moderating effect of entrepreneurial education on the relationship between the internal environment and entrepreneurial innovation was found to be insignificant. The findings provide valuable insight for not just higher education institutions offering entrepreneurial education courses in the UAE. Nevertheless, for entrepreneurship stakeholders globally understanding how to enhance the significant role of entrepreneurial education on external and internal factors will ensure higher innovativeness among international students in the host country.